kết quả rút gọn biểu thức
-3x+\(\sqrt{25^2}\)(x<0)
a.-2x
b.8x
c.-8x
d.2x
giúp tớ voii
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\frac{x}{y}.\frac{x}{y^2}=\frac{x^2}{y^3}\left(\text{vì }x>0;y< 0\text{ nên: }\frac{x}{y^2}>0\right)\)
\(A=\frac{x}{y}\cdot\sqrt{\frac{x^2}{y^4}}=\frac{x}{y}\cdot\frac{\sqrt{x^2}}{\sqrt{y^4}}=\frac{x}{y}\cdot\frac{\left|x\right|}{\left|y^2\right|}=\frac{x}{y}\cdot\frac{x}{y^2}=\frac{x^2}{y^3}\)( x > 0 ; y < 0 )
\(1,=0,9\left|x\right|\\ 2,Sửa:\dfrac{\sqrt{63y^3}}{\sqrt{7y}}=\sqrt{\dfrac{63y^3}{7y}}=\sqrt{9y^2}=3\left|y\right|=-3y\)
\(-\dfrac{\sqrt{x^2}}{x}=\dfrac{-\left|x\right|}{x}=\dfrac{-x}{x}=-1\)(Vì x>0 nên |x|=x)
\(\dfrac{\sqrt{a^3}}{\sqrt{a}}=\dfrac{a\sqrt{a}}{\sqrt{a}}=a\)(với a>0)
Với a>0 ta có:
\(\dfrac{\sqrt{a^3}}{\sqrt{a}}=\dfrac{\sqrt{a^2\cdot a}}{\sqrt{a}}=\dfrac{\left|a\right|\cdot\sqrt{a}}{\sqrt{a}}=a\)( vì \(a>0\Rightarrow\left|a\right|=a\))
\(A=\frac{y}{x}\cdot\sqrt{\frac{x^2}{y^4}}=\frac{y}{x}\cdot\frac{\sqrt{x^2}}{\sqrt{y^4}}=\frac{y}{x}\cdot\frac{\left|x\right|}{\left|y^2\right|}=\frac{y}{x}\cdot\frac{x}{y^2}=\frac{1}{y}\)( x > 0 ; y > 0 )
`(\sqrt(3x^2-12x+12)-x+2)/(x-2)`
`=(\sqrt(3(x^2-4x+4))-(x-2))/(x-2)`
`=(\sqrt(3(x-2)^2)) -(x-2))/(x-2)`
`=(\sqrt3. (x-2) - (x-2))/(x-2)`
`=( (\sqrt3-1) (x-2))/(x-2)`
`=\sqrt3-1`
`=>` C.
\(=\dfrac{1}{y-x}\cdot x^3\cdot\left(x-y\right)=-x^3\)
Sửa đề: \(-3x+\sqrt{25x^2}\)
\(=-3x+\sqrt{\left(5x\right)^2}\)
\(=-3x-5x\left(x< 0\right)\)
=-8x
=>Chọn C